ANALISIS KADAR KAFEIN PADA KOPI BUBUK DI KOTA BENGKULU MENGGUNAKAN SPEKTROFOTOMETRI ULTRAVIOLET - Elly Mulyani (Politeknik Medica Farma Husada Mataram, 2019)
Caffeine is one type of alkaloid found in coffee beans, tea leaves, and chocolate seeds. The aim of this research was to find out the caffeine content in local ground coffee taken from the center of souvenir sales in the city of Bengkulu by the ultraviolet spectrophotometry method. The sample was extracted with a separating funnel using chlorophrom solvents. The results of caffeine levels obtained from 6 samples have met the requirements of SNI 01-3542-2004 which is between 0.45-2% b / b. In percent (b / b) then every 1 gram of local ground coffee contains caffeine levels of 2.03%, 1.73%, 1.19%, 0.71%, 1.91%, and 0.14% . Calculation of caffeine levels in one cup of local ground coffee samples (per 6 grams / once serving) are 122.2215 mg, 104.274 mg, 71.568 mg, 42.9735 mg, 114.8685 mg ,and 8.6595 mg. Consumption of ground coffee as much as 3-4 servings in one day, the caffeine content is entered in the usual dosage of Indonesian Pharmacopoeia (300-600 mg).